Coronavirus: A Practicing Veterinarian Prospective - Mazhar Ayaz Muhammad; Mudasser Nazir Muhammad; Saleem Akhtar Muhammad; Aziz Mubashir; Niaz Kamal; Ahmad Tanveer; Ahmad Haroon; Sattar Sheikh Ahsan (International Journal of Coronaviruses, 2020)
COVID19 is posing threat cosmopolitically encompassing more than 200 countries and making threat to entire population globally as pandemic. The cats, dogs and bovine are at threat which are close partner to human population. The veterinarians specially practicing are at risk when they encounter the sick animals. This study focus to the Pakistani veterinarian where animal population is under estimated or sometimes census is not performed. As Current population of domestic animals in Pakistan consist of 23.34 million buffaloes, 22.42 million cattle, 24.24 million sheep, 49.14 million goats, and with a huge population of dogs and cats without official census which may pose a threat to innocent population and even more a practicing veterinarian and veterinary paramedics are more at threat, if god forbids. There is need for further investigation its role and zoonotic perspective. Regarding practicing field veterinarians fighting without weapons against mass destructing pathogen and making vulnerability on wide.
Keywords: Covid-19